Characterization of ultrastructure and collagen composition of the teratoma membrane: Comparison to the amniotic membrane. Issue 4 (11th February 2013) - Kim, Kyung Sook; Cho, Chang‐Hoon; Kim, Young‐Sun; Yoon, Kyung‐Sik; Jung, Min‐Hyung; Park, Hun‐Kuk
ABSTRACT The structural and morphological properties of the teratoma membrane were investigated to better understand the pathogenesis of ovarian teratomas. A mature cystic teratoma and amnion were obtained from patients who underwent laparoscopic cystectomy and uncomplicated delivery, respectively. The teratoma membrane was divided into three layers according to the results of the histological analysis. Each layer showed distinct morphological properties, including an outer layer that was uniformly arranged, a middle layer with an irregular pattern of fibers, and an inner layer that was structurally dense with a wavy pattern of fibers. The morphology of the layers of the amniotic membrane was the reverse that of the teratoma membrane. In the teratoma membrane, the outer layer was primarily composed of type III collagen and the inner layer had a large amount of type III and IV collagen. The amniotic membrane showed a small amount of type III collagen in the outer layer, whereas the inner layer had large amounts of type I, III, and IV collagen. In the teratoma membrane, the collagen fibrils were arranged regularly in the outer layer, but irregularly in the inner layer. In the amniotic membrane, the arrangement of collagen fibrils was the reverse that of the teratoma membrane. Additionally, the collagen fibrils in the teratoma membrane were thinner than those of the amniotic membrane and had slightly shorter d‐spacing. Two membranes showed the differences in collagen fibril arrangement, which may caused by the different functional roles. Microsc. Res. Tech. 76:432–441, 2013. © 2013 Wiley Periodicals, Inc.